The Development of Illustrated Storybooks on Theme 2 Subjects in Improving the Social Character of Students at MI PPI Bintang Sembilan Batat - Rosyidah , Faizatur (MANDAILING GLOBAL EDUKASIA, 2024)
This research developed a picture fairy tale book to improve the social character of class III MI PPI Bintang Sembilan Batat students in the thematic subject theme 2, against the backdrop of changes in the Indonesian curriculum that included character education and concerns about the lack of social interaction among students due to the influence of devices. This R&D research uses the Borg and Gall model with interview, observation, and questionnaire data collection methods. The results of the research show that the application of illustrated fables using illustrations, the development of illustrated fairy tale books follows the development procedure, and students show enthusiasm and understanding of character values. The increase in students' social concern after the use of picture story books can be seen from the increase in the average value of attitude from 66.97% to 87.10%.